The Line - a City in the Desert. A Laboratory of Hyper-Modernity and Two Visions of the Future - Matysek-Imielińska, Magdalena (Porównania, 2024)
In 2022, the Pritzker Prize jury recognized the work and activities of architect Francis Kéré, pointing out its responsible and sustainable nature, use of local materials, and exhibited vernacular knowledge. In a similar vein, the theme of the 18th Architecture Biennale was “Laboratory of the Future.” It was pointed out that it is African architecture that excels in conditions of scarcity and climate crisis, and that in this sense it is experimental. Because future is already happening in Africa. These two examples serve as a starting point for showing that the world of global and mainstream architecture has a clear interest in restrained, sustainable, local architecture. Meanwhile, in Saudi Arabia, The Line is being built—a hyper-modern, futuristic linear megacity that disregards climatic, industrial, as well as cultural and social contexts. This work juxtaposes two visions of cities of the future and—from the perspective of cultural urban studies—analyzes the way the city is understood, deconstructing its futuristic character and confronting it with the growing criticism of civilizationally and technologically advanced architecture and urbanism, which is seeing increasing issues with eliminating the irrational solutions and building techniques it itself produces (discourse surrounding the smart city, the zero-carbon city, the myth of clean energy sources). Using Tim Ingold’s proposals, The Line is analyzed in the context of inhabitation rather than building, process rather than product. It is juxtaposed with architecture that was meant to be communal as opposed to individualized—fitting buildings into their natural surroundings as opposed to starchitecture that disregards landscape, social and cultural contexts. One wonders if The Line’s design takes into account practical urban issues and their human dimension or whether it is solely focused on style, spectacular form, generating profits, and reproducing social inequality. The city of The Line thus is found to be a non-place (Marc Augé).